QUESTIONNAIRE FOR STUDENTS FROM FACULTIES OF DENTAL MEDICINE IN BULGARIA REGARDING THEIR MOTIVATION FOR PARTICIPATION IN AND THE WAY THEY ARE FAMILIAR WITH RESEARCH PROJECTS. - Svetoslav Garov; Maria Dencheva; Angelina Kisselova (Peytchinski Publishing, 2013)
Introduction: In recent years there has been a significant increase in the number and value of projects implemented by medical universities in Bulgaria. The involvement of representatives of the student community in the research teams increases their knowledge and skills and in this way they also gain experience in team work and become motivated to further develop their science careers. Aim: The purpose of our study is by analyzing data from our questionnaire to examine the level of students' willingness to participate in research project activities performed by Bulgarian faculties of Dental Medicine. Material and methods: The written examination technique has been applied as a primary empirical sociological information registration method. For that purpose a 13-question survey (questionnaire) has been prepared. The survey is anonymous and it has been completed by 190 students in their 4th and 5th year of studying in medical universities in Sofia, Plovdiv and Varna. Data was collected during the period from January to May 2013. Results: In order for us to achieve the goal of this study we focused on the questions from the questionnaire.Conclusion: The role that research projects play in medical universities and in particular in the faculties of dental medicine in Bulgaria is of key importance for their accreditation. The scientific cooperation between lecturers and students is a prerequisite for developing a competitive environment that defines the future scientific achievements in the relevant research institution.